Factors that cause non-performing loan in microfinance at Bank Simpanan Nasional Kelantan / Nik Zatil Aqmar Nik Faudzi - Nik Faudzi, Nik Zatil Aqmar (2011)
Danny Yap (2010) reported that, the non-performing loans ratio (NPLs) in Malaysia is expected to come under pressure this year (2011) as the country faces a more challenging global and domestic environment. Thus, this research was conducted to study the factors that cause to non-performing loan (NPL) in Microfinance at Bank Simpanan Nasional Kelantan. The objective of this research is to determine the factors that cause non-performing loan (NPL) and the relationship between the independent variables (the unpredictable crises among borrowers, the operation management, the analysis on credit scoring and the attitude of borrowers) and dependent variable (Non-Performing Loan). The researcher has distributed the questionnaire to the staff at Bank Simpanan Nasional Kelantan especially who have been involved in Micro Finance/ Micro Credit. The Pearson Analysis is used to measure the strength of the association between two variables. The result indicate that the strength of association between IV1 (r = 0.934) and IV4 (r = 0.948) are very high and very strong and that the correlation coefficient are very highly significantly different from zero (p<0.01). Hence, the result above has answered the objective of the research. Several actions will be taken by the bank onto NPL borrowers either do litigation; LOD, NOT, Summon, or Judgment. The NPL borrowers also suggested to do reschedule and refinancing (R&R), Workout Proposal, Capitalize, or Write-off to lighten the NPL borrower’s burden